Design, simulation, and adjustment of the longitudinal–torsional composite integrated ultrasonic variable amplitude system - Cunying Zhang; Bo Zhao; Ying Niu (Advances in Mechanical Engineering, 2018)
For the longitudinal–torsional composite integrated ultrasonic variable amplitude system with the longitudinal–torsional resonance produced by helical slots in the cone of the launch section, the theoretical design, finite element simulation, and experimental study are carried out. The performed analysis of the helical slot structural characteristics revealed that slot depth, helical angle, and slot width have a strong effect on the natural frequency and ratio of the torsional–longitudinal amplitude. A credible technique for adjusting the deviation of the actual system natural frequency from the theoretical design value by traditional method is proposed based on the adjustment theory of non-uniform medium adopted. The experimentally proved reduction of the above deviation strongly suggests that the approach proposed in this article provides effective theoretical guidance and experimental basis for the study of longitudinal–torsional composite integral ultrasonic variable amplitude system.